Optimalisasi pengolahan limbah diapers bayi berbasis ekonomi sirkular berkelanjutan dengan pemodelan sistem dinamis di Kota Surabaya - Sakti, Yuni Krida (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The problem of baby diapers waste is currently an environmental issue globally. Especially in big cities, one of which is the city of Surabaya. Because diapers waste is difficult to decompose naturally, it requires innovative and sustainable management optimization. By implementing circular economy programs through the Diapers Waste Bank and non-governmental organizations, it is hoped that it will be able to reduce the pile of diapers waste and improve the economic welfare of the local community. This study aims to predict the reduction of diapers waste piles and the economic value of diapers waste within a period of 13 years, Data from 2020 to 2033 by optimizing the effectiveness of the Waste Bank and involving community participation in recycling programs and as customers. With a dynamic system modeling approach, it is known that the increase in diapers waste reduction in 2033 will be able to reach 1,2085.68 tons with an initial value of 64.98 tons with an effectiveness rate of 57% and a customer growth rate of 45% and an economic value of around 10 billion rupiah. If the optimization reaches 80%, it can achieve the zero waste target.